Matrix metalloproteinases in lung health and disease, volume 3, The role of matrix metalloproteinases in cystic fibrosis lung disease - Gaggar, Amit; Hector, Andreas; Bratcher, P. E.; Mall, Marcus A.; Griese, Matthias; Hartl, Dominik (The European respiratory journal, 2011)
Significant airway remodelling is a major component of the increased morbidity and mortality observed in cystic fibrosis (CF) patients. These airways feature ongoing leukocytic inflammation and unrelenting bacterial infection. In contrast to acute bacterial pneumonia, CF infection is not cleared efficiently and the ensuing inflammatory response causes tissue damage. This structural damage is mainly a result of free proteolytic activity released by infiltrated neutrophils and macrophages. Major proteases in this disease are serine and matrix metalloproteases (MMPs). While the role of serine proteases, such as elastase, has been characterised in detail, there is emerging evidence that MMPs could play a key role in the pathogenesis of CF lung disease. This review summarises studies linking MMPs with CF lung disease and discusses the potential value of MMPs as future therapeutic targets in CF and other chronic lung diseases.
Gesehen am 12.07.2023
Angabe zum Entstehungsdatum auf der Frontdoor: Online veröffentlicht 31. August 2011, frühere Fassung vom 13. Januar 2011